Emerging roles and potential application of PIWI-interacting RNA in urological tumors - Zhang, Jingcheng; Zhang, Wentao; Liu, Yuchao; Pi, Man; Jiang, Yufeng; Ainiwaer, Ailiyaer; Mao, Shiyu; Chen, Haotian; Ran, Yuefei; Sun, Shuwen; Li, Wei; Yao, Xudong; et al. (Frontiers in Endocrinology, 2023)
The piRNA (PIWI-interacting RNA) is P-Element induced wimpy testis (PIWI)-interacting RNA which is a novel small molecule, non-coding RNA with a length of 24-32nt. It was originally found in germ cells and is considered a key regulator of germ cell function. It can interact with PIWI protein, a member of the Argonaute family, and play a role in the regulation of gene transcription and epigenetic silencing of transposable factors in the nucleus. More and more studies have shown that piRNAs are abnormally expressed in a variety of cancer tissues and patient fluids, and may become diagnostic tools, therapeutic targets, staging markers, and prognostic evaluation tools for cancer. This article reviews the recent research on piRNA and summarizes the structural characteristics, production mechanism, applications, and its role in urological tumors, to provide a reference value for piRNA to regulate urological tumors.